Pengaruh Aplikasi Arang Sekam dan Pupuk Organik Cair terhadap Pertumbuhan Tanaman Pakcoy (Brasicca rapa L.) - Mujiono Mujiono; Rosi Widarawati; Budi Supono (Proceedings Series on Physical & Formal Sciences, 2021)
This research aims to determine: 1) the effect of the comparison of the use of husk charcoal growing media with soil on the growth of pakcoy plants, 2) the effect of the application of liquid organic fertilizer (SO-Kontan Fert) on the growth of pakcoy plants, 3) the effect of a combination of rice husk planting media with soil and POC (SO-Kontan Fert) application to the growth of pakcoy plants. This research was conducted from January to March 2020 at the screen house of Melung Village, Baturraden District, Banyumas Regency, Central Java and the Agronomy and Horticulture Laboratory of the Faculty of Agriculture, Jenderal Soedirman University, with Andisol soil types. The experimental design used was a completely randomized block design (RAKL) with a 2-factor factorial design. The first factor is husk charcoal (M), namely, M0 = without husk charcoal, M1 = soil + husk charcoal (1: 1), M2 = soil (2: 1), soil + husk charcoal (3: 1). The second factor is the concentration of POC SO-Kontan Fert (P), namely, P0 = 0 ml POC SO-Kontan Fert / Lt water, P1 = 5 ml POC SO-Kontan Fert / Lt water, P2 = 10 ml POC SO-Kontan Fert / Lt water, P3 = 15 ml POC SO-Kontan Fert / Lt water. Results of the research showed that giving husk charcoal to pakcoy plant media at a ratio of 3: 1 was able to increase plant height by 47.19 cm and leaf length by 26.13 cm ,. A ratio of 2: 1 can increase leaf greenness by 2.8 units. The application of liquid organic fertilizer (SO-Kontan Fert) with a concentration of 5 ml / l was able to increase the number of leaves by 6.59.